(untitled) (Journal of Philosophy Culture and Political Science, 2021)
Abstract: The article examines the process of transformation of the culture of watching cinema and the relationship of viewers with cinemas in a pandemic. An analysis is made of how the film audience of Kazakhstan will change during and after the pandemic. In the changed conditions created by the pandemic, it is necessary to identify the factors and motivations that lead viewers to watch films in or outside the cinema. In connection with the pandemic situation, the survey used the survey method (WebSurvey). The survey was conducted using an interactive questionnaire posted on the website and filled out from a computer or mobile device in the online survey mode. No restrictions were imposed at the time of the survey, except that the minimum age of the participants had to be 18 years old. One of the main objectives of this study in terms of moviegoer research is to analyze the changing culture of film viewing in Kazakhstan at a time when online platforms and the pandemic have significantly changed the collective viewing experience. According to the study, the coronavirus pandemic is directly and indirectly affecting viewers and movie-watching culture in a variety of ways. Keywords: cinema, pandemic, new media, audience studies, film audience